2012
DOI: 10.1242/bio.2012653
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spheroid budding from monolayers: a potential contribution to ovarian cancer dissemination

Abstract: SummaryOvarian cancer is the most lethal gynaecologic cancer, in large part because of its early dissemination and rapid development of chemotherapy resistance. Spheroids are clusters of tumor cells found in the peritoneal fluid of patients that are thought to promote this dissemination. Current models suggest that spheroids form by aggregation of single tumor cells shed from the primary tumor. Here, we demonstrate that spheroids can also form by budding directly as adherent clusters from a monolayer. Formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…The EMT phenotype is also associated with the formation of multicellular spheroids. Recently, Pease et al . reported spontaneous formation of 3D aggregates budding from monolayers of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EMT phenotype is also associated with the formation of multicellular spheroids. Recently, Pease et al . reported spontaneous formation of 3D aggregates budding from monolayers of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The EMT phenotype is also associated with the formation of multicellular spheroids. Recently, Pease et al 52 reported spontaneous formation of 3D aggregates budding from monolayers of ovarian cancer cells. Interestingly, these buds lacked cortical E-Cadherin, could effectively detach from the monolayer, and survived even in the presence of commonly used cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of spheroids is another characteristic feature of ovarian cancer metastasis (37). Spheroids provide an evolutionary advantage in tumor progression as they are less sensitive to chemotherapy due to up-regulation of B-cell leukemia-xL (BCL-xL) (38).…”
Section: Transcoelomic Metastasis Of Ovarian Carcinomamentioning
confidence: 99%
“…Spheroids provide an evolutionary advantage in tumor progression as they are less sensitive to chemotherapy due to up-regulation of B-cell leukemia-xL (BCL-xL) (38). In addition, they exhibit pronounced capacity to adhere to components of the ECM and mesothelial cells (37). Tumor cells in spheroids are also protected against antitumoral immune effector cells (29,30 (30).…”
Section: Transcoelomic Metastasis Of Ovarian Carcinomamentioning
confidence: 99%
“…As Achilli et al (2012) recently described, there are at least 7 other culturing conditions that will result in the formation of spheroids by lessening contact between cells and surfaces such as the plastic surface of petri dishes. Furthermore, and relevant to our discussion, there is at least one paper showing that ovarian cancer cells in a monolayer can give rise to multicellular solid spheroids spontaneously and that these are released into the medium following a period of being tethered to the monolayer that produced them (Pease et al 2012).…”
Section: Multicellular Hollow Spheroidsmentioning
confidence: 99%